2021
DOI: 10.3390/su13052506
|View full text |Cite
|
Sign up to set email alerts
|

Driving Mechanism of Farmers’ Utilization Behaviors of Straw Resources—An Empirical Study in Jilin Province, the Main Grain Producing Region in the Northeast Part of China

Abstract: In recent years, the unsustainable behaviors of straw utilization have led to waste straw being one of the sources of agricultural non-point source pollution. Studying the resource utilization of crop straw is conducive to expediate the development of ecological and green agriculture. More importantly, it has long-term significance for the recycling of agricultural waste, improving the quality of rural life, and the employment of farmers. Based on the theory of planned behavior (TPB), taking the representative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…In addition, a reduction in the fragmentation of cultivated land is achieved. (2) Resource utilization behavior is an indirect factor affecting the evolution of agricultural production space [39]. With the increase in the likelihood of a peasant household understanding policy, acquiring up-to-date information, and undergoing industrial technology training, resource utilization has shifted from simplification to modernization and specialization, and the choices regarding a peasant household's production behavior have been further affected [40], which can support adjustments to the spatial quantity and distribution of cultivated land.…”
Section: Spatial Scale Volatility Decrease: Transformation Of Peasant...mentioning
confidence: 99%
“…In addition, a reduction in the fragmentation of cultivated land is achieved. (2) Resource utilization behavior is an indirect factor affecting the evolution of agricultural production space [39]. With the increase in the likelihood of a peasant household understanding policy, acquiring up-to-date information, and undergoing industrial technology training, resource utilization has shifted from simplification to modernization and specialization, and the choices regarding a peasant household's production behavior have been further affected [40], which can support adjustments to the spatial quantity and distribution of cultivated land.…”
Section: Spatial Scale Volatility Decrease: Transformation Of Peasant...mentioning
confidence: 99%
“…Farmers’ intention and behavior of straw returning technology. Referring to the research of Lu et al (2020) and Guo et al (2021) , the adoption intention of farmers’ straw returning technology is characterized from two aspects: adoption intention and promotion intention. The measurement items are based on Likert’s 5-point scale, and the answer options for all questions are “very low,” “lower,” “average,” “higher,” and “very high,” which are assigned “1–5,” respectively.…”
Section: Data Variables and Modelmentioning
confidence: 99%
“…Therefore, farmers’ subjective cognitive factors have attracted more and more attention in recent years. Guo et al (2021) analyzed that the behavioral attitude, subjective norms, perceived behavioral control, and moral responsibility of farmers have a significant positive impact on the intention to use straw resources. Li et al (2020) found that perceived value and perceived benefit had a significant positive impact on farmers’ intention to produce green agriculture, while perceived risk had a significant negative impact.…”
Section: Introductionmentioning
confidence: 99%
“…TPB theory better explains the relationship between environmental behaviour and willingness of farmers [ 47 ], so it has been widely used in the research of farmers’ environmental behaviour and willingness. The willingness of farmers for ecological protection could significantly promote the behaviour of farmers for ecological protection [ 49 , 50 ], and willingness was a key factor that affected the actual environmental behaviour of farmers [ 51 ]. Hines et al analysed 128 types of environmental behaviours and found that environmental cognition could significantly affect individual environmental behaviours [ 52 ].…”
Section: Literature Analysismentioning
confidence: 99%
“…In waste sorting and processing, although individuals with high cognition were more inclined to take participatory behaviours [ 53 ], the deviation between environmental cognition and behaviour [ 54 ] made cognition inaccurately predict individual behaviour. When using TPB theory to analyse farmers’ participation in behaviour, scholars found that farmers’ behaviours and attitudes could not only indirectly affect actual behaviour through willingness, but it also has a significant direct impact on actual behaviour [ 50 ]. Studies have found that attitudes play a mediating role in the influence of variables such as environmental awareness and environmental care on the governance of rural human settlements [ 55 ].…”
Section: Literature Analysismentioning
confidence: 99%